Work-life systems: integrating endurance and uncertainty in future work - Griffin, Mark (2019)
The nature of work is rapidly evolving as technological, demographic, and economic changes influence all aspects of our society. The changing nature of work requires a more wholistic understanding of work life systems that encompasses work tasks, non-work, and sleep across longer time spans. In this presentation I explore two concepts through which research is extending the understanding of work-life systems. First, studies of endurance provide new insights into the long-term impact of demanding work in complex environments. I review research involving two very different work environments: submariners in the Navy and FIFO workers in mining. Both populations highlight psychological and physical challenges best viewed from the perspective of complete work-life systems. Second, I explore the role of uncertainty in future work. Uncertainty is a defining feature of complex, and high-risk work and often viewed as contextual feature of the work context. I review recent research investigating uncertainty as a more dynamic element of work-life that is both generated and managed when there is ongoing adaptive behaviour. I propose a new model of how individuals both respond to and generate uncertainty to be adaptive.